2020
DOI: 10.4045/tidsskr.20.0299
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 med stille hypoksemi

Abstract: Luftambulanseavdelingen Oslo universitetssykehusWilliam Ottestad er spesialist i anestesiologi og overlege. Forfatteren har fylt ut ICMJE-skjemaet og oppgir ingen interessekonflikter. MARI SEIMTårnåsen Legesenter Mari Seim er lege i spesialisering i allmennmedisin. Forfatteren har fylt ut ICMJE-skjemaet og oppgir ingen interessekonflikter. JENS OTTO MAEHLEN AnestesiavdelingenAkershus universitetssykehus Jens Otto Maehlen er spesialist i anestesiologi og overlege. Forfatteren har fylt ut ICMJE-skjemaet og oppgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
95
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 5 publications
1
95
0
10
Order By: Relevance
“…10 Ottestad et al first reported this entity in an elderly man with COVID-19 who developed rapidly progressive respiratory failure with severe hypoxia, although having no significant respiratory distress at presentation. 3 Later, Wilkerson et al described a 72-year-old man with COVID-19 who presented with minimal respiratory symptoms and very low oxygen saturation; the patient eventually died due to progressive respiratory decompensation and multiorgan dysfunction. 16 The unusual clinical picture of hypoxia out of proportion to the respiratory distress in our patient and the aforementioned review of literature emphasise the importance of identifying the subtle clinical signs which are often missed.…”
Section: Discussionmentioning
confidence: 99%
“…10 Ottestad et al first reported this entity in an elderly man with COVID-19 who developed rapidly progressive respiratory failure with severe hypoxia, although having no significant respiratory distress at presentation. 3 Later, Wilkerson et al described a 72-year-old man with COVID-19 who presented with minimal respiratory symptoms and very low oxygen saturation; the patient eventually died due to progressive respiratory decompensation and multiorgan dysfunction. 16 The unusual clinical picture of hypoxia out of proportion to the respiratory distress in our patient and the aforementioned review of literature emphasise the importance of identifying the subtle clinical signs which are often missed.…”
Section: Discussionmentioning
confidence: 99%
“…Another key area that can be monitored using data from EMS systems during the COVID-19 pandemic is the detection of "silent hypoxia". Reports from China, and later Italy, the US, and Norway, have described many COVID-19 patients who initially present with hypoxemia without signs of respiratory distress ("silent hypoxemia") and later go on to develop respiratory failure [18][19][20][21] . It is possible that this kind of hypoxemia, and subsequent rapid decompensation 22 , could result in mortality before patients are able to access EMS or hospital services, especially in areas were health systems are saturated or patients are not able to quickly access healthcare services when decompensation occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Over 80% of COVID-19 patients in the intensive care unit have severe hypoxemia 7 . A kind of "silent hypoxia" in which COVID-19 patients deteriorate rapidly without warning and develop respiratory failure has been described 8 . Hypoxia indicates an imbalance of oxygen delivery to tissues and leads to compromised function, which is quantitatively related to organ, tissue and even cell type 9 .…”
Section: Introductionmentioning
confidence: 99%